Ambient energy harvesting by ZnO thin film - Yit, Pei Shian (2016)
This thesis deals with ambient energy harvesting using zinc oxide thin film. The objectives of this thesis are to prove the ZnO film as a piezoelectric material can produce electric when vibration is applied and determine its optimal voltage. This thesis describes the sol gel spin coating technique to fabricate zinc oxide thin film. Zinc acetate dehydrate, absolute ethanol and diethanolamine were used to act as sol gel precursor. Sol gel was coated on glass slide which wrapped by aluminum foil. The thin film was formed after preheating and annealing. The thin film was characterized by X-ray diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM), Photoluminescence Spectroscopy (PL) and Ultraviolet-visible Spectroscopy (UV-Vis) as well as analyzed using vibration technique. From XRD results, the films were preferentially diffracted at around 65° which corresponding to (1 1 2) diffraction phase. From FESEM results, it was observed that when the spin speed was increased at same annealing temperature, the thickness was also decreased. When the annealing temperature was increased at same spin speed, both grain size and thickness were increased. From the PL results, there was only film with spin speed of 2000 rpm and annealing temperature of 300°C had slightly left wavelength which was 380 nm. Annealing temperature would affect only the intensity of PL wavelength. From the results of UV-Vis, it was observed that when the spin speed was increased at same annealing temperature, the band gap was decreased. When the annealing temperature was increased at same spin speed, the band gap was decreased. Piezoelectric test had proven the ZnO film could produce electricity. The maximum voltage (20.7 mV) was produced by the ZnO film with spin speed of 2000 rpm and annealing temperature of 300°C.